Management of persistent anal canal carcinoma after combined-modality therapy: a clinical review - Musio, Daniela; De Felice, Francesca; Raffetto, Nicola; Tombolini, Vincenzo (Radiation oncology (London, England), 2014)
Anal canal carcinoma is a rare gastro-intestinal cancer. Radiochemotherapy is the recommended primary treatment for patients with non-metastatic carcinoma; surgery is generally reserved for persistent or recurrent disease. Follow-up and surveillance after primary treatment is paramount to classify patients in those with complete remission, persistent or progressive disease. Locally persistent disease represents a clinically significant problem and its management remains subject of some controversy.The aim of this systematic review is to summarise recommendations for the primary treatment of anal canal carcinoma, to focus on the optimal time to consider residual disease as genuine persistence to proceed with salvage treatment, and to discern how this analysis might inform future clinical trials in management in this class of patients.